An investigation into linguistic features of participants in the processes in english and vietnamese from the functional grammar aspect (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The system of transitivity (or process type) classifies the world of experiential meaning into different types of process, each of which is associated with certain functional participant roles, occurring in different configuration. The study attempted to describe linguistic features of participants in the processes in English and in Vietnamese to find out the similarities and differences between the two languages. With the purpose of making an investigation into the syntax and semantics of the participants in English and Vietnamese, the study was carried out basing on comparative and descriptive approaches. The data were grouped into categories depending on their syntactic and semantic features. The researcher observed and investigated the data taken from different sources in English and Vietnamese equivalent, examines how they were used and described them. As a result, some potential problems in learning will be pointed out and solved because not all the distinguished features of participants are the same in both languages.